Recent progress in cathode interlayer materials for non‐fullerene organic solar cells - Ahmad, Nafees; Zhou, Huiqiong; Fan, Ping; Liang, Guangxing (EcoMat (Beijing, China), 2022)
Non‐fullerene acceptors are currently a hot research area in the development of organic solar cells (OSCs). At present, the‐state‐of‐the‐art power conversion efficiency (PCE) of non‐fullerene organic solar cells (NF‐OSCs) with single and multiple‐junction has surpassed 18% and 19%, respectively. The cathode interlayer (CIL) plays a significant role in the improvement of PCE and the stability of OSCs. Recently, a large number of CIL materials have been employed in OSCs. This review summarizes the recent progress of CIL materials and systematically describes their impact on the device efficiency and stability in single‐junction NF‐OSCs. Firstly, the functions, key requirements, and distinctive features of CILs when used in NF‐OSCs are summarized. Afterward, some big families of materials including metal oxides, metal salts/complexes, small molecules, polymers, composites/hybrids are presented as CIL for NF‐OSCs. Finally, the scale‐up techniques, conclusion, and future challenges regarding CIL in NF‐OSCs are elucidated. This review summarizes the recent advances of cathode interlayer (CIL) materials and systematically describes their impact on the device efficiency and stability in single‐junction non‐fullerene‐based organic solar cells (NF‐OSCs). The functions, key requirements, and distinctive features of CILs when used in NF‐OSCs are discussed, along with the scale‐up techniques and future challenges in this area of research.